2022
DOI: 10.3389/fgene.2022.858466
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of the Diagnostic Characteristic Genes of Ovarian Cancer by Bioinformatics and Machine Learning

Abstract: Background: Ovarian cancer (OC) has a high mortality rate and poses a severe threat to women’s health. However, abnormal gene expression underlying the tumorigenesis of OC has not been fully understood. This study aims to identify diagnostic characteristic genes involved in OC by bioinformatics and machine learning.Methods: We utilized five datasets retrieved from the Gene Expression Omnibus (GEO) database, The Cancer Genome Atlas (TCGA) database, and the Genotype-Tissue Expression (GTEx) Project database. GSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The immunohistochemical staining of the glycolytic risk genes in lymphoma patients and normal controls was obtained from the Human Protein Atlas (HPA) database ( http://www.proteinatlas.org/ ) ( Liu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The immunohistochemical staining of the glycolytic risk genes in lymphoma patients and normal controls was obtained from the Human Protein Atlas (HPA) database ( http://www.proteinatlas.org/ ) ( Liu et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Up to 90% of OC, especially the HGSOC type, overexpress FOLR1 [ 87 , 89 ], and FOLR1 expression is closely associated with the severity of OC ( Figure 14 ) [ 79 , 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…Machine learning algorithms and bioinformatics can also be used to analyze multiple large gene datasets to identify and validate genes with a potential diagnostic value. Liu et al [ 226 ] have focused on OC genome exploration based on Gene Expression Omnibus (GEO), the Cancer Genome Atlas (TCGA), and the Genotype-Tissue Expression (GTEx) cohort datasets, with the application of machine learning algorithms. Moreover, the authors have investigated the function and pathways that are involved in the interdependence between those characteristics, diagnosis-related genes, and immune cell infiltration in OC to be analyzed at a later stage [ 226 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…Additionally, the authors investigated whether DEGs and immune cell infiltration could be related. According to the study results, out of 590 identified DEGs, 10 genes, i.e., budding uninhibited by benzimidazoles 1 (BUB1), adenosine 5′-triphosphate–binding cassette subfamily B member 1 (ABCB1), secreted frizzled-related protein 1 (SFRP1), innate immunity activator (INAVA), transmembrane protein 139 (TMEM139), mitotic checkpoint serine/threonine-protein kinase BUB1 beta (BUB1B), phosphoserine aminotransferase 1 (PSAT1), phosphodiesterase 8B (PDE8B), folate receptor alpha (FOLR1), and homeobox A13 (HOXA13), are involved in biological cell functions and could affect immune infiltration levels in OC [ 226 ].…”
Section: Future Directionsmentioning
confidence: 99%